PENGEMBANGAN E-KOMIK BERBASIS KEARIFAN LOKAL PADA MATERI MELESTARIKAN BUDAYA BANGSAKU DALAM MATA PELAJARAN PPKN KELAS VIII SMP - Amanda, Zikratul; Rayendra; Pratiwi, Rahmi; Masriani, Elsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of engaging and contextual learning media in Civic Education learning, particularly on the topic of preserving national culture. The integration of local wisdom values into learning activities was also still limited. Therefore, this study aimed to develop a local wisdom-based e-comic for the topic “Melestarikan Budaya Bangsaku” in Grade VIII Civic Education learning. This research employed a Research and Development (R&D) approach using the 4-D model, consisting of Define, Design, Develop, and Disseminate stages. Product validation was conducted by one material expert and two media experts, while practicality testing involved 30 Grade VIII students at SMP Negeri 22 Padang. The results showed that the material validation score reached 94.6%, categorized as “Very Valid”. Media validation results reached 99% from media expert I and 97.2% from media expert II, both categorized as “Very Valid”. The practicality test obtained an average score of 4.62, categorized as “Very Practical”. These findings indicate that the developed local wisdom-based e-comic is highly valid and practical for use in Civic Education learning.